Roles of LncRNAs in Regulating Mitochondrial Dysfunction in Septic Cardiomyopathy - Liu, Shuang; Chong, Wei (Frontiers in Immunology, 2021)
Sepsis is an abnormal systemic inflammatory response of the host immune system to infection and can lead to fatal multiorgan dysfunction syndrome. Epidemiological studies have shown that approximately 10-70% of sepsis cases can lead to septic cardiomyopathy. Since the pathogenesis of septic cardiomyopathy is not clear, it is difficult for medical doctors to treat the disease. Therefore, finding effective interventions to prevent and reduce myocardial damage in septic cardiomyopathy is clinically significant. Epigenetics is the study of stable genetic phenotype inheritance that does not involve changing gene sequences. Epigenetic inheritance is affected by both gene and environmental regulation. Epigenetic studies focus on the modification and influence of chromatin structure, mainly including chromatin remodelling, DNA methylation, histone modification and noncoding RNA (ncRNA)-related mechanisms. Recently, long ncRNA (lncRNA)-related mechanisms have been the focus of epigenetic studies. LncRNAs are expected to become important targets to prevent, diagnose and treat human diseases. As the energy metabolism centre of cells, mitochondria are important targets in septic cardiomyopathy. Intervention measures to prevent and treat mitochondrial damage are of great significance for improving the prognosis of septic cardiomyopathy. LncRNAs play important roles in life activities. Recently, studies have focused on the involvement of lncRNAs in regulating mitochondrial dysfunction. However, few studies have revealed the involvement of lncRNAs in regulating mitochondrial dysfunction in septic cardiomyopathy. In this article, we briefly review recent research in this area.